Determinants of Life Expectancy and its Prospects Under the Role of Economic Misery: A Case of Pakistan - Nanthakumar, Loganathan; Muhammad, Shahbaz; Nooreen, Mujahid (Springer Netherlands, 2015)
The present study investigates the determinants of life expectancy in the presence of economic misery using Pakistan’s time series data over the period of 1972-2012. The stationary properties of the variables are examined by applying unit root test accommodating structural breaks. The ARDL bounds testing approach to cointegration is applied to examine the long run relationship between the variables. Our findings show that cointegration between the variables is confirmed. Moreover, health spending improves life expectancy. Food supply contributes to life expectancy. A rise in economic misery deteriorates life expectancy. Urbanization enhances life expectancy while illiteracy declines it. The causality analysis reveals that life expectancy is Granger cause of health spending, food supply, economic misery, urbanization and illiteracy. This paper opens up new insights for policy making authorities to consider the role of economic misery while formulating comprehensive economic policy to improve life expectancy in Pakistan.